PENGARUH ETIKA PROFESIONAL, AKUNTABILITAS, KOMPETENSI DAN DUE PROFESSIONAL CARE TERHADAP KUALITAS AUDIT - Mustikawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to test the influence of professional ethic, accountability, competency and due professional care to the audit quality. Based on the calculation obtains that determination coefficient value R2(R Square) of 0.691 show that professional ethic, accountability, competency, due professional care are able to explained the audit quality approximately 69.1%, while the rest is of 30.9% explained by the other variable of this research. While, based on the hypothesis test obtain that professional ethic, accountability, competency, due professional care have an influence to the audit quality.Keywords: professional ethic, accountability, competency, due professional care and audit quality.